2010
DOI: 10.1007/s12020-010-9346-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression in ACTH-producing pituitary tumors: up-regulation of microRNA-122 and -493 in pituitary carcinomas

Abstract: MicroRNAs (miRNAs) are involved in cell proliferation, differentiation, and apoptosis, and can function as tumor suppressor genes or oncogenes. The expression of miRNAs in pituitary carcinomas has not been previously examined. We used miRNA profiling with 1,145 probes to study miRNA expression in normal anterior pituitary (6 cases), adrenocorticotropin (ACTH)-producing adenomas (8 cases), and ACTH-producing pituitary carcinomas (two cases). Real-time RT-PCR and in situ hybridization were used to confirm and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 36 publications
1
48
0
5
Order By: Relevance
“…[35][36][37] The possible involvement of miRNAs in human pituitary tumors has also been reported. Stilling et al 38 profiled miRNA expression using a microarray technique and found that 188 miRNAs are up-regulated and 160 miRNAs are down-regulated in corticotroph adenomas, compared with normal pituitaries. Bottoni et al 39 reported that expression of miR-15a and of miR-16-1 is significantly reduced in both corticotroph adenomas and prolactinomas.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] The possible involvement of miRNAs in human pituitary tumors has also been reported. Stilling et al 38 profiled miRNA expression using a microarray technique and found that 188 miRNAs are up-regulated and 160 miRNAs are down-regulated in corticotroph adenomas, compared with normal pituitaries. Bottoni et al 39 reported that expression of miR-15a and of miR-16-1 is significantly reduced in both corticotroph adenomas and prolactinomas.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that Stilling et al 81 found that miR-493 was significantly underexpressed in functional ACTHPAs compared to that in the normal pituitary gland. miR-493 is a known tumor-suppressor miRNA.…”
Section: Mirna Expressionmentioning
confidence: 94%
“…Kimutatták továbbá, hogy a miR-141-et gyengén expresszáló ACTH-termelő adenomák esetében nagyobb a sebészeti eltávolítás utáni gyógyulás aránya [40]. Egy másik munkacsoport szintén ACTH-termelő agyalapimirigy-daganatok vizsgálata során kimutatta, hogy a miR-122 és a miR-493 erősebben fejeződik ki carcinomában, mint adenomában és normálszövetben, ami arra utal, hogy ezeknek a miRNS-eknek szerepük lehet a malignitás kialakulásában is [41].…”
Section: Mirns-expressziós Eltérések Az Agyalapimirigy-daganatokbanunclassified